Knowledge and Perception towards Pharmacovigilance among Healthcare Professionals in Tertiary Care Teaching Hospital in Aden, Yemen - Alshakka, Mohammed; Bassalim, Huda; Alsakkaf, Khaled; Mokhtar, Marwa; Alshagga, Mustafa; AL-Dubai, Sami; Jha, Nisha; Abdoraboo, Ahmed; Shanker, P. Ravi (Journal of Pharmacy Practice and Community Medicine)
Reporting adverse drug reactions (ADRs) is considered the essence of pharmacovigilance practice. Physician and nurse are among health care providers who extensively take part in reporting. However, underreporting is a malpractice worldwide. This study aimed to determine physicians and nurses’ knowledge and perception toward pharmacovigilance in general, and consumer’s related pharmacovigilance. Method: A cross-sectional study was conducted in Al-Gamhouria Teaching Hospital at Aden, Yemen. The study conducted from September to October 2014. Target populations were physicians and nurses. A 40-item self administered questionnaire was administered among participants. Descriptive and Chi square analysis were used to analyse to express the results. Results: 130 health care professionals were participating in the study with a mean age of 42.9 (SD7.93) years and a mean experience period of 20.3 (SD 9.73). Females comprised 63.1% of the participants and majority of them are nurses (68.5%). Although, Physicians and nurses showed varied statistically significant differences in knowledge toward pharmacovigilance. However, nurses showed a positive attitude and perception. Meanwhile, regarding consumer pharmacovigilance, again nurses showed positive attitude compared to physicians but physicians were more positive with the consumer reporting. Both physicians and nurses were highly scored for the importance of pharmacovigilance in Yemen as well as to be part of health education curriculum. Conclusion: A relatively good level of pharmacovigilance knowledge has been encountered among physicians and nurses. Nurses had had optimistic attitude and higher perception toward pharmacovigilance compared to physicians who more valued consumer reporting.
Keywords: Knowledge; Perception; ADRs reporting; pharmacovigilance; physician; nurses; Yemen